2012
DOI: 10.6002/ect.2012.0013
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Matrix Metalloproteinases and Their Inhibitors in Kidney Transplant Recipients

Abstract: Objectives: Chronic allograft nephropathy remains one of the main causes of late graft loss after kidney transplant owing to multifactorial development of kidney scarring. Chronic allograft nephropathy is characterised by an excess accumulation of extracellular matrix. A key system regulating extracellular matrix homeostasis are matrix metalloproteinases and tissue inhibitors of matrix metalloproteinases. This study sought to determine if a change in the matrix metalloproteinases/tissue inhibitors of matrix me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…Wang et al have shown that TIMP-3 protects the cells from damage, whereas TIMP-2 appears to promote injury through matrix metalloproteinase activation [ 32 ]. Similarly, research studies in renal transplant allografts show that matrix metalloproteinase activity is important in mediating scarring in chronic allograft nephropathy [ 33 ].…”
Section: Two Sides To Cell-cycle Arrestmentioning
confidence: 99%
“…Wang et al have shown that TIMP-3 protects the cells from damage, whereas TIMP-2 appears to promote injury through matrix metalloproteinase activation [ 32 ]. Similarly, research studies in renal transplant allografts show that matrix metalloproteinase activity is important in mediating scarring in chronic allograft nephropathy [ 33 ].…”
Section: Two Sides To Cell-cycle Arrestmentioning
confidence: 99%
“…While TIMP-3 is required for optimal response to renal injury, TIMP-2 appears to promote disease progression through the activation of matrix metalloproteinase and triggering of tubulointerstitial fibrosis and injury. Similarly, research studies in renal transplant allografts show that matrix metalloproteinase activity is important in mediating scarring in chronic allograft nephropathy [ 37 ].…”
Section: Biological Role Of the Cell Cycle Biomarkersmentioning
confidence: 99%
“…Η έκφραση των TIMPs αυξάνεται από κυτταροκίνες (IL-1,-6,-11), αυξητικούς παράγοντες (TGF-β, Vascular Endothelial Growth Factor -VEGF) και ορμόνες39,40 . Η ισορροπία MMPs/TIMPs είναι ιδιαίτερα κρίσιμη για την εύρυθμη αναδιαμόρφωση των ιστών και η διαταραχή της σχέσης αυτής φαίνεται να εμπλέκεται σε πολλές παθολογικές διεργασίες, όπως αθηροσκλήρωση, ίνωση, νεοαγγειογένεση όγκων και μετάσταση[39][40][41][42][43][44][45][46][47][48][49] . Αρχικά θεωρήθηκε ότι οι MMPs αποδομούν μόνο τις πρωτεΐνες της ECM, κυρίως το col-IV, κύριο συστατικό των αγγείων και της BM, το οποίο διαδραματίζει κυρίαρχο ρόλο στην έναρξη και εξέλιξη της νεφρικής νόσου, καθώς και στην αθηροσκλήρωση24,42,43 .…”
unclassified